Sensitive Skin Syndrome in Children with Atopic Dermatitis: Pathogenesis and Management Features - Nikolay N. Murashkin; Roman V. Epishev; Dmitri V. Fedorov; Alexander I. Materikin; Eduard T. Ambarchyan; Leonid A. Opryatin; Alena A. Savelova; Roman A. Ivanov; Wasel Ahmad (Вопросы современной педиатрии)
The atopic dermatitis (AD) is common skin disease and has significant impact on patients and their families quality of life. In recent years the term “sensitive skin" has been used more frequently. It is separate syndrome with subjective perception (such as burning, itching, tingling, etc.) along with thickening and dryness of the skin in response to environmental factors (biotic, abiotic and anthropogenic) which normally do not cause such symptoms. This syndrome is often associated with AD. The AD and sensitive skin syndrome pathogenesis and their management are presented in the article. Efficiency and safety parameters of pimecrolimus 1% cream in children (including its appliance on sensitive skin areas) are analysed.